Waveguide polaritons: interaction of a quantum well exciton with an electromagnetic mode of a planar waveguide - Beggs, DM; Kaliteevski, MA; Brand, S; Abram, RA; Kavokin, AV (physica status solidi (c), 2005)
A transfer matrix method has been used to calculate the dispersion relations of planar dielectric waveguides containing quantum well excitons. It is found that waveguide polaritons are formed, whose dispersion displays the classic anti-crossing behaviour at the exciton resonance frequency. For a quantum well placed at the anti-node of the fundamental TE mode of the waveguide considered, the Rabi-splitting is calculated to be 6.55 meV, with waveguide polaritons of lifetimes of ∼7 ps, corresponding to a displacement along the waveguide axis of ∼0.3 mm.
EPrint Processing Status: Publisher does not permit full text to be deposited
Keywords: 42.79.Gn; 71.35.–y; 71.36.+c; 78.20.Bh; 78.67.De.